Become Captain of Your Financial Ship: A Curriculum in Financial Management - Josephine Turner (EDIS)
FCS7220, a 2-page fact sheet by Josephine Turner, introduces readers to this series on personal financial management and describes the four core units: Charting the Course, Trimming the Sails, Standing Watch, and Stay the Course. Published by the UF Department of Family, Youth and Community Sciences, January 2007.